Sensitivity of Colletotrichum acutatum Isolates from Citrus to Carbendazim, Difenoconazole, Tebuconazole, and Trifloxystrobin - Gama, Andre B.; Baggio, Juliana S.; Rebello, Carolina S.; Lourenco, Silvia de Afonseca; Gasparoto, Maria Candida de G. [UNESP]; Silva Junior, Geraldo Jose da; Peres, Natalia A.; Amoriml, Lilian (Amer Phytopathological Soc, 2020)
Postbloom fruit drop (PFD) of citrus is caused by the Colletotrichum acutatum and C. gloeosporioides species complexes. The disease is important when frequent rainfall occurs during the flowering period of citrus trees. In Brazil, until 2012, PFD was mainly controlled by preventive applications of the methyl-benzimidazole carbamate (MBC) carbendazim and demethylation-inhibitor (DMI) fungicides such as difenoconazole. Since then, mixtures containing the DMI tebuconazole and the quinone-outside inhibitor (QoI) trifloxystrobin have been commonly used. Fungicides are often applied preventively, sometimes even when conditions are not conducive for PFD development. Excessive fungicide applications may favor the selection of resistant populations of Colletotrichum spp. In this study, we assessed the fungicide sensitivity of C. acutatum isolates collected during the two distinct periods of PFD management in Brazil: before and after the trifloxystrobin and tebuconazole mixture became widely employed. The sensitivity of 254 C. acutatum isolates to carbendazim and difenoconazole and of 164 isolates to tebuconazole and trifloxystrobin was assessed. Mycelial growth inhibition of these isolates was evaluated for all the fungicides using either serial dilution of fungicide rates or the spiral gradient dilution method. In addition, inhibition of conidial germination was also assessed for trifloxystrobin. Analysis of partial beta-tub, cytb, and cyp51b gene sequences did not reveal any mutations related to resistance to MBCs, QoIs, and DMIs, respectively. In mycelia] growth assays, mean EC50 values were 0.14, 0.11, and 0.21 mu g/ml for difenoconazole, tebuconazole, and trifloxystrobin, respectively. The conidial germination inhibition by trifloxystrobin was similar among the tested isolates, and the mean EC50 value was 0.002 mu g/ml. All isolates had similar mean mycelial growth inhibition for carbendazim, regardless of the fungicide concentrations. Therefore, based on similar EC50 values and molecular analyses, no shift in the sensitivity of isolates has been observed to the fungicides commonly used in different citrus-producing areas in Brazil.
Keywords: postbloom fruit drop; fungicide resistance; baseline